Administration of Nivolumab in Metastatic Renal Cell Cancer Following Treatment With mTOR Inhibitors - Kopecky, Jindrich; Kubecek, Ondrej; Buchler, Tomas; Melichar, Bohuslav; Poprach, Alexandr; Zemanova, Milada; Katolicka, Jana; Kiss, Igor; Hajek, Jaroslav; Studentova, Hana; Spisarova, Martina (In vivo (Athens, Greece), 2021)
BACKGROUND/AIM: Immunotherapy with checkpoint inhibitors is currently considered a cornerstone of metastatic renal clear cell cancer (mRCC) therapy. Despite the general improvement in the survival of patients with mRCC, there are some clinical situations that have not been specifically evaluated in clinical trials, such as the use of everolimus before nivolumab. PATIENTS AND METHODS: We performed a retrospective analysis evaluating the efficacy of nivolumab in the real-world setting, including a subset of patients with previous mTOR inhibitor therapy. RESULTS: From a total of 56 patients, 25 were pre-treated with everolimus before receiving nivolumab. The overall progression-free survival (PFS), overall survival (OS), and objective response rate were 10.3, 21.3 months, and 34%, respectively. There were no statistically significant differences in patients who were or were not pre-treated with everolimus. CONCLUSION: mRCC patients should be treated with checkpoint inhibitors and prior use of mTOR inhibitors should not be a definitive exclusion criterium.
Keywords: Carcinoma, Renal Cell; Retrospective Studies; lidé; výsledek terapie; karcinom z renálních buněk; systematic inflammation index; Kidney Neoplasms; neutrophil-lymphocyte ratio; Nivolumab; platelet-lymphocyte ratio; retrospektivní studie; Humans; TOR Serine-Threonine Kinases; TOR serin-threoninkinasy; nivolumab; Treatment Outcome; mTOR inhibitor; nádory ledvin; Renal cell cancer